2021
DOI: 10.1108/tqm-06-2021-0161
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality performance in the Egyptian manufacturing industry

Abstract: PurposeThe purpose of this study was to examine the quality performance of the Egyptian manufacturing industry based on Flynn's quality management practices framework.Design/methodology/approachA literature-based questionnaire was developed to collect the research data. The sample studied included 193 professionals from different manufacturing firms in Egypt. The research model utilized seven first-order constructs to measure infrastructure and core quality practices and the model was analyzed by structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…The study performed statistical analysis and found that 20 organizational performance indicators such as delivery performance, quality performance, inventory level and sales turnover. Further, ElMelegy et al. (2022) assessed quality performance in manufacturing organization based in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…The study performed statistical analysis and found that 20 organizational performance indicators such as delivery performance, quality performance, inventory level and sales turnover. Further, ElMelegy et al. (2022) assessed quality performance in manufacturing organization based in Egypt.…”
Section: Introductionmentioning
confidence: 99%